PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE INDEX CARD MATCH UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SD NEGERI 004 GENDUANG KECAMATAN PANGKALAN LESUNG KABUPATEN PELALAWAN - Umi Kalsum; Hamizi '; Erlisnawati ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : One of study aim accomplishment achievement height learns student. but evaluation result during teach, show from 30 students, 10 students (33%) not yet achieve criteria value ketuntasan minimal (kkm) in batural sciences subject at class iv that is 70 or with result presents in low category averagely class as big as 62.97. This Reseach this carried out on 2 up to 18 Aprils 2015 with 2 cycles. subjek watchfulness teacher and class student iv country elementary school 004 genduang regency mortar landing stage district pelalawan, with total 30 students, consist of 14 mans and 16 womans. data collecting instrument in sikripsi this teacher activity sheet and student with result test exercise learns. berdasarkn watchfulness result, inferential that type co-operative study model index card match can increase result learn class student batural sciences iv country elementary school 004 genduang regency mortar landing stage district pelalawan as that is: seen from result learns score base as big as 62,97 increase in my cycle is averagely 72.17 happen enhanced 9.20. in cycle ii average 78,00 with good category increases to be 5.83 from average score base. student is mobileer in learn, cooperate in discussion group and also increase student responsibility taste towards matter that studied.Key Words: Model Learning Index Card Match, grade students Achievement.